Corporate Governance and Firm-Specific Crash Risk: Evidence from Indonesian Firms in 2016 - Sihombing, Yosua; Diyanty, Vera (Jurnal Akuntansi dan Bisnis, 2019)
This research is aimed at investigating whether several dimensions of corporate governance mechanism, namely family ownership, accounting opacity, and Board of Commissioners effectiveness, have effect on one-year-ahead stock price crash risk. Hypothesis test is conducted in 2017 using cross section regression analysis with 277 samples of non-financial firms listed on Indonesia Stock Exchange in 2016. The result of this research does not show that family ownership and accounting opacity have any effect on firm-specific crash risk. Moreover, the result of this research finds that Board of Commissioners effectiveness has negative effect on firm-specific crash risk. This finding supports the notion that sound corporate governance system increases monitoring activities. This, in turn, decreases the tendency of managers to hide and accumulate bad news from outsiders. Hence, reducing firm-specific crash risk. Penelitian ini bertujuan untuk menginvestigasi apakah tiga dimensi mekanisme tata kelola perusahaan, kepemilikan keluarga, accounting opacity dan efektivitas Dewan Komisaris, berdampak terhadap 1-year-ahed stock price crash risk. Penelitian ini menemukan bahwa efektivitas Dewan Komisaris berpengaruh negatif terhadap firmspecific crash risk. Temuan ini mendukung suatu pernyataan bahwa sistem tata kelola perusahaan yang baik dapat meningkatkan kegiatan pemantauan. Hal ini pada akhirnya akan mengurangi kecenderungan manajer untuk menyembunyikan berita buruk dari outsiders. Namun Demikian, penelitian belum ditemukan bukti yang mendukung hubungan antara kepemilikan keluarga dan opacity akuntansi dan firm-specific crash risk.